2012
DOI: 10.1088/1054-660x/23/1/016001
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–plasma plume investigation during high-power fiber laser welding

Abstract: This work is devoted to the investigation of the laser-matter interaction during up to 20 kW ytterbium fiber laser welding of thick mild steel plates. The plume attenuation of a probe 1.3 µm wavelength diode laser beam as well as of continuous radiation in the 250-600 nm wavelength range was measured during welding with and without Ar shielding gas supply. The measured results allow the calculation of the average size and concentration of fine condensed metal particles in different plume areas using the multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…The laser powder bed fusion process is always performed under inert atmosphere, in order to avoid any possible interaction between the metal particles (very reactive with a high specific surface area) and impurities such as humidity and light elements (i.e., oxygen, carbon oxides), which might affect the local chemical composition and the resulting mechanical properties of the manufactured parts [18,23,58]. Furthermore, a continuous flow of inert gas is essential in order to limit the redeposition on the powder bed of by-products during the process; this is crucial because should the removal of by-products by the shielding gas flow not be effective, there is a high risk of laser attenuation [97][98][99].…”
Section: Shielding Gas Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…The laser powder bed fusion process is always performed under inert atmosphere, in order to avoid any possible interaction between the metal particles (very reactive with a high specific surface area) and impurities such as humidity and light elements (i.e., oxygen, carbon oxides), which might affect the local chemical composition and the resulting mechanical properties of the manufactured parts [18,23,58]. Furthermore, a continuous flow of inert gas is essential in order to limit the redeposition on the powder bed of by-products during the process; this is crucial because should the removal of by-products by the shielding gas flow not be effective, there is a high risk of laser attenuation [97][98][99].…”
Section: Shielding Gas Flowmentioning
confidence: 99%
“…It must be pointed out that, if a large amount of condensate is generated and eventually redeposited on the bed together with the ejected (spatter) particles, the surface properties of the powder will change and might influence the flowability of the reused feedstock material [101,135,136]. From Figure 10, it is possible to observe that condensate is in the form of nanoparticles since, during the cooling, there is a decrease in metal vapor solubility in the process chamber environment, giving rise to a supersaturated solution with high undercooling, a condition which fosters the formation of nanoparticles [39,97,98,126,137]. These results suggest that the reuse of powders with condensate content should be prevented, but more studies specifically focused on this topic are needed in order to monitor the condensate formation and evolution for different alloys.…”
Section: Condensatementioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the slender plume is created by the shining particles as the laser beam heats them during high-power fiber laser welding [28]. According to the experimental results shown in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Shcheglov et al [12] observed two characteristic parts of the plume when laser welding mild steel (Fig. 1).…”
Section: Introductionmentioning
confidence: 95%